2005
DOI: 10.1111/j.1365-2141.2005.05868.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐DRB1 polymorphism is associated with Kell immunisation

Abstract: Summary K immunisation is observed in some polytransfused patients and pregnant women but does not occur in all cases of K incompatibility. This study analysed the role of genetic background in this selective response to K antigen by investigating HLA‐DRB1 alleles associated with K immunisation in a southern European population. HLA‐DRB1 genotyping was performed by polymerase chain reaction sequence‐specific oligonucleotide/sequence‐specific primer procedures in 54 K immunised patients and 200 healthy controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
62
1
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 20 publications
7
62
1
4
Order By: Relevance
“…Immunogenetics plays some role in variability of alloimmunization to blood products, as antibody responses to certain alloantigens are confined to distinct recipient human leukocyte antigen (HLA) types. [6][7][8] In addition, genetic variants outside of HLA may regulate RBC alloimmunization. 9 Environmental differences between recipients also likely affect alloimmunization, as genetically identical animals still have variable alloantibody responses to transfused RBCs.…”
Section: Introductionmentioning
confidence: 99%
“…Immunogenetics plays some role in variability of alloimmunization to blood products, as antibody responses to certain alloantigens are confined to distinct recipient human leukocyte antigen (HLA) types. [6][7][8] In addition, genetic variants outside of HLA may regulate RBC alloimmunization. 9 Environmental differences between recipients also likely affect alloimmunization, as genetically identical animals still have variable alloantibody responses to transfused RBCs.…”
Section: Introductionmentioning
confidence: 99%
“…The binding groove formed by the various MHC class II genes has a variable affinity for different peptides, with consequences for peptide presentation to T-cells. Recent studies showed that, within a particular ethnic group, the intrinsic immunogenicity of a given red cell antigen is, amongst other factors, related to the presence of particular HLA-DRB1* molecules, capable of effective binding and presentation of blood group derived peptides to CD4 T lymphocytes [89][90][91][92] .…”
Section: Immunogenicitymentioning
confidence: 99%
“…After phagocytosis, the RBC antigens are proteolysed into small peptide fragments in lysosomes and short linear segments of 12-28 amino acids are associated with newly formed HLA class II molecules in postlysosomal vesicles. Genetic HLA class II restriction determines which peptides are tightly bound in the HLA class II groove 90,92,[106][107][108] . The peptide/HLA complex is transported to the plasma membrane of the macrophage where they are presented to TCR and immunoglobulin receptors on B-cells 109,110 .…”
Section: Alloimmune Response To Red Blood Cell Antigensmentioning
confidence: 99%
“…For example, HLA DRB1*04 and DRB1*15 are associated with immunization to the FY1 Ag [10,11], HLA-DRB1*01 and DRB1*10 are associated with immunization to the JK1 Ag [12], and DRB1*11 and DRB1*13 are associated with immunization to the KEL1 Ag [13]. Therefore, antigen immunogenicity varies depending on the receiver HLA typing, as some HLA molecules are better fitted to present an immunogenic peptide than others, while RH1 is probably more immunogenic, because it is a truncated protein, so numerous peptides can be presented by the recipient immune system.…”
Section: The Immunogenicity Of Foreign Agsmentioning
confidence: 99%